2022
DOI: 10.9758/cpn.2022.20.1.17
|View full text |Cite
|
Sign up to set email alerts
|

Psychobiotic Therapy: Method to Reinforce the Immune System

Abstract: Psychobiotics are probiotic microorganisms that beneficially affect the central nervous system functions mediated by the gut-brain axis, improving the host's immune system. Psychobiotic microorganisms can regulate brain pathways and serotonin production (mood controller). The main microbial genera with psychobiotic characteristics are Lactobacillus, Lactococcus and Bifidobacterium. The daily consumption of psychobiotics is called "Psychobiotic Therapy". Psychobiotic therapy has proven antidepressant/anxiolytic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 60 publications
0
14
0
Order By: Relevance
“…The gut microbiome influences human health in a number of ways, from mediating early life immune system development [1,2], to determining personalized responses to nutritional interventions [3,4] and influencing the central nervous system [5,6]. Stool transit time, defined as the rate at which stool moves through the gastrointestinal tract, is a major determinant of the composition of the human gut microbiota [7].…”
Section: Introductionmentioning
confidence: 99%
“…The gut microbiome influences human health in a number of ways, from mediating early life immune system development [1,2], to determining personalized responses to nutritional interventions [3,4] and influencing the central nervous system [5,6]. Stool transit time, defined as the rate at which stool moves through the gastrointestinal tract, is a major determinant of the composition of the human gut microbiota [7].…”
Section: Introductionmentioning
confidence: 99%
“…Since biogenic amines, such as serotonin, could be involved in the antisenescence effects of probiotic bacteria ( 10 , 39 ), live FC modifies the number of monoamines absorbed and influences senescence through the so-called gut-brain axis ( 40 ). FC might function as a psychobiotic bacterium in worms ( 41 ). Although it remains uninvestigated whether the organisms can produce bioactive amines, another probiotic, Bifidobacterium dentium , has been reported to stimulate serotonin synthesis in chromaffin cells ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…In response to inflammatory stimuli, the HPA axis secretes corticotropin‐releasing hormone (CRH) and adrenocorticotrophic hormone (ACTH). These hormonal substances are essential for starting immunological reactions against various microbes such as viruses (Oroojzadeh et al, 2022), bacteria (Salem et al, 2022), and fungi (Magalhães‐Guedes, 2022). Prior studies have shown that CRH can increase the permeability of the intestines and increase levels of ACTH in the circulation when there is neuronal stress.…”
Section: Neuronal Pathways For Gut‐brain Axis Interactionsmentioning
confidence: 99%